Improved Glycerol Electrooxidation at Carbon-Supported PdFe Bimetallic Catalysts - Bresciani, Guilherme Bueno; Franco, Jefferson Honorio [UNESP]; Kokoh, K. Boniface; Napporn, Teko W.; De Andrade, Adalgisa R. [UNESP] (The Electrochemical Society, 2023)
We have investigated glycerol electrooxidation at Pd/C and PdFe/C catalysts, synthesized by the microwave polyol decomposition method. Five different heating ramps were tested to provide active catalyst nanoparticles and desired metal loadings at 20 wt%. Introducing iron in the Pd/C catalyst composition improved the catalytic activity and stability of the anode. The PdFe/C catalysts presented greater oxidative capacity and contributed efficiently to the keeping of glycerol skeleton reaction products. The analytical techniques composed of liquid chromatography coupled with mass spectrometry (LC-MS) confirmed glycerate, glycolate, formate, tartronate, and oxalate as the main glycerol oxidation products. The bi-metallic catalysts (PdFe/C) harvested electrons from glycerol and produced energy more effectively than the catalyst without iron (Pd/C). Glycerol proved a potential platform for generating high value-added products and can be employed as a renewable clean energy source for electrosynthesis purposes and fuel cell applications.